Struktur Pasar BBM (Bahan Bakar Minyak) di Indonesia: Peran Monopoli, Skandal Korupsi, dan Prospek Implementasi Blockchain - Suci Ananda Febrianti; Septiana Sihombing; Rahmalia Maharani; Mardila Saputri; Mozaik Plamonia Ramadhan (Jurnal Multidisiplin Ibrahimy, 2025)
Pertamina’s monopoly over aviation fuel and domestic fuel markets drives high prices and poor fuel quality, exacerbated by systemic issuesw This study examines the impacts of Pertamina’s monopoly, using a literature review, simple regression, and real-time data from Trading Economics, Statista, ESDM, supported by 10 monopoly-focused journals. The 2025 corruption scandal (Rp 193.7 trillion loss) reinforces monopolistic inefficiencies, with overpriced imports (Rp 11.7 trillion) strengthening avtur dominance, raising aviation costs by 10-15%. Monopoly-driven quality omission increases pollution by 8% (Rp 8 trillion health costs). Global oil prices fell 13.86% (Brent USD 64.35/barrel, June 2025), but domestic fuel prices only dropped 4.85% (Pertalite Rp 12,100/liter) due to monopolistic pricing and low elasticity (0.35). Weak KPPU oversight and UU No. 5/1999 enforcement worsen inefficiencies. Blockchain-based supply chain transparency could reduce losses by 20-30%, fostering competition.